Clinical significance of unfavorable findings in intermediate‐risk prostate cancer patients for predicting treatment outcomes after contemporary, dose‐escalated multimodal radiotherapy. Issue 4 (16th December 2021) - Urabe, Fumihiko; Miki, Kenta; Kimura, Takahiro; Sasaki, Hiroshi; Tashiro, Kojiro; Tsutsumi, Yuki; Morikawa, Midoriko; Minato, Kyosuke; Sato, Shun; Takahashi, Hiroyuki; Aoki, Manabu; Egawa, Shin
Abstract: Purpose: Few studies have documented the long‐term oncological outcomes of favorable and unfavorable intermediate‐risk (IR) prostate cancer patients treated via contemporary high‐dose irradiation. We analyzed the ultimate clinical outcomes of such patients using the current risk sub‐stratification schema. Patients and Methods: We included 693 patients with localized IR prostate cancer treated via low‐dose‐rate brachytherapy (LDR‐BT) with or without external beam radiation (EBRT) and with or without androgen‐deprivation therapy (ADT) in a single institution. Treatment outcomes (biochemical recurrence‐free survival [BCRFS] and clinical progression‐free survival [CPFS]) were compared according to the numbers of unfavorable findings. Results: Out of the 693 IR patients, 292 (42.1%) exhibited favorable disease; the remaining 401 (57.9%) exhibited unfavorable disease. Compared with favorable IR status, unfavorable IR status was associated with shorter BCRFS and CPFS ( p < 0.001 and p < 0.001, respectively). Patients with two to three unfavorable factors experienced the worst oncological outcomes ( p < 0.001 and p < 0.001). Although patients with one or no unfavorable factors responded similarly to LDR‐BT monotherapy, this treatment modality was insufficient for preventing biochemical and clinical progression in patients with multiple unfavorable findings. Conclusion: Long‐term treatment outcomes indicate that patients with IR disease scheduled for LDR‐BT should undergo multimodal irradiation if they exhibit two or more unfavorable factors at diagnosis.